ปัจจัยที่มีผลต่อการปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐานของอาสาสมัครสาธารณสุขประจำหมู่บ้าน จังหวัดสุโขทัย - Yaebkai, Yutthana (วารสารวิจัยการพยาบาลและสุขภาพ, 2018)
การวิจัยครั้งนี้เป็นการวิจัยเชิงพยากรณ์ มีวัตถุประสงค์เพื่อศึกษา 1) ความรู้ เจตคติ การรับรู้บทบาท แรงสนับสนุนทางสังคม แรงจูงใจในการปฏิบัติงาน และการปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐานของอาสาสมัครสาธารณสุขประจำหมู่บ้าน และ 2) ปัจจัยที่มีผลต่อการปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐาน และความสามารถของปัจจัยด้านความรู้ เจตคติ การรับรู้บทบาท แรงสนับสนุนทางสังคมแรงจูงใจในการปฏิบัติงาน และปัจจัยส่วนบุคคลในการพยากรณ์การปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐานของอาสาสมัครสาธารณสุขประจำหมู่บ้าน กลุ่มตัวอย่างคือ อาสาสมัครสาธารณสุขประจำหมู่บ้าน จังหวัดสุโขทัย จำนวน 223 คน ได้จากการสุ่มตัวอย่างแบบเป็นระบบ เก็บรวบรวมข้อมูลด้วยแบบสอบถาม สถิติที่ใช้วิเคราะห์ข้อมูล ได้แก่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์ถดถอยพหุแบบขั้นตอน ผลการวิจัยพบว่า ความรู้ เจตคติ การรับรู้บทบาท แรงสนับสนุนทางสังคม แรงจูงใจในการปฏิบัติงาน และการปฏิบัติงานอยู่ในระดับสูง ปัจจัยที่มีผลต่อการปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐานของอาสาสมัครสาธารณสุขประจำหมู่บ้าน เรียงลำดับตามความสามารถในการอธิบายความแปรปรวนของการปฏิบัติงานจากมากไปหาน้อย ได้ดังนี้ 1) แรงจูงใจในการปฏิบัติงาน มีผลทางบวกต่อการปฏิบัติงานสามารถอธิบายความแปรปรวนได้ร้อยละ 48.7 (R Square = 0.487) 2) การรับรู้บทบาท มีผลทางบวกต่อการปฏิบัติงานสามารถอธิบายความแปรปรวนได้เพิ่มขึ้นร้อยละ 6.0 เป็นร้อยละ 54.7 (R Square Change = 0.060, R Square = 0.547) และ 3) แรงสนับสนุนทางสังคม มีผลทางบวกต่อการปฏิบัติงานสามารถอธิบายความแปรปรวนได้เพิ่มขึ้นร้อยละ 2.4 เป็นร้อยละ 57.0 (R Square Change = 0.024, R Square = 0.570) โดยสามารถร่วมกันพยากรณ์การปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐานของอาสาสมัครสาธารณสุขประจำหมู่บ้านได้ ร้อยละ 57.0 อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 ผลการวิจัยครั้งนี้ สามารถนำไปใช้พัฒนาการปฏิบัติงานตามมาตรฐานงานสาธารณสุขมูลฐานของอาสาสมัครสาธารณสุขประจำหมู่บ้านให้มีประสิทธิภาพและประสิทธิผลมากยิ่งขึ้น โดยการสร้างแรงจูงใจในการปฏิบัติงาน การรับรู้บทบาท และแรงสนับสนุนทางสังคม Factors Affecting towards the Performance on Village Health Volunteers’ Standard of Primary Health Care, Sukhothai Province The purpose of this predictive research was to study 1) the knowledge, attitude, perception on roles, social support, motivation, and performance on village health volunteers’ standard of primary health care, and 2) investigate factors affecting towards the performance on village health volunteers’ standard of primary health care, and the knowledge, attitude, perception on roles, social support, motivation, and personal factors in predicting factors affecting towards the performance on village health volunteers’ standard of primary health care. The samples were 223 village health volunteers in Sukhothai Province. They were selected by using systematic random sampling technique. In this research, questionnaire was employed for data collection, and the data were analyzed by using percentage, mean, standard deviation, and stepwise multiple regression analysis. The results revealed that the knowledge, attitude, perception on roles, social support, motivation, and performance were at high level. Factors affecting towards the performance on village health volunteers’ standard of primary health care were ordered, from maximum to minimum, for predicting the variances of performances, as follows: 1) motivation had positive effect on the performances, and it could explain the variance at 48.7 % (R Square = 0.487) 2) the perception of roles had positive effect on the performances, and it could explain the variance at 6.0 % which accounted for 54.7 % in predicting performances (R Square Change = 0.060, R Square = 0.547), and 3) the social support had positive effect on the performances, and it could explain the variance at 2.4 % and accounted for 57.0 % in predicting performances (R Square Change = 0.024, R Square = 0.570). These factors could predict the performances at 52.8 % with statistical significance at the level of p < 0.05. The results of this research can be useful to use develop performance on village health volunteers’ standard of primary health care efficiently and effectively should seriously focus on the motivation, perception on roles, and social support.